EVALUATION OF BIOLOGICAL ACTIVITY OF GREENLY SYNTHESIZED SILVER NANOPARTICLES USING ALOE VERA GEL EXTRACT AS ANTIBACTERIAL AGENT IN-VITRO AND IN-VIVO - & et al., Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present study was carried out to synthesis silver nanoparticles by using Aloe Vera gel and evaluates antibacterial activity in vitro and in vivo. The synthesis and characterization of silver nanoparticles was confirmed by Ultra Violet Visible- spectrophotometer, X-ray diffraction, Fourier Transmission Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy. Reduction of the Ag+ to Ag0 during exposure to the Aloe Vera gel extract was followed by color change of the solution from colorless, yellow to dark brown within 24 hours. It is observed that surface Plasmon resonance peaks of the maximum absorbance of silver-nanoparticles occur at 425 nm, indicating that AgNPs were produced. Later on, using agar well diffusion and tube dilution method against pathogenic methicillin resistance staphylococcus aureus, (MRSA). Pseudomonas. aeruginosa and Escherichia coli, the antimicrobial properties of synthesised AgNPs were investigated. To confirm in-vivo antibacterial activity, after inducing complicated skin and soft tissue infection in mice by injecting S.aureus subcutaneously. 16µg/gm AgNPs were applied skin infected daily for three days. Silver nanoparticles were as succeeded to reduce the lesion volume in infected mice and reduce the acute inflammation symptoms as clindamycin, In conclusion, A new approach can be used to combat serious infections caused by MRSA by Aloe Vera AgNPs.